Evolving Antithrombotic Treatment Patterns for Patients With Nonvalvular Atrial Fibrillation and Acute Coronary Syndrome or Underwent Percutaneous Coronary Intervention in China: A Cross-Sectional Study - Suo, Ni; Yang, Yan-min; Wang, Juan; Zhang, Han; Shao, Xing-hui; Wu, Shuang; Zhu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Objective Antithrombotic therapy in patients with non-valvular atrial fibrillation (NVAF) concomitant with acute coronary syndrome (ACS) or underwent percutaneous coronary intervention (PCI) is challenging and has evolved in recent years. However, real-world data on this issue about antithrombotic regimens at discharge and its evolving trend was relatively scarce, especially in China. Methods 2182 patients with NVAF and ACS/PCI were enrolled from 2017 to 2019. 1979 patients were finally analyzed and divided in three sequential cohorts: Cohort 1 (2017), n=674; Cohort 2 (2018), n=793; Cohort 3 (2019), n=512. Baseline characteristics and antithrombotic therapy at discharge were analyzed by cohort. Results In our cross-sectional study, the majority of patients (59.6%) received dual antiplatelet therapy (DAPT). Over the three years, DAPT prescription reduced from nearly 70% to less than 50%（P trend<0.001）, while triple therapy (TT) / double therapy (DT) increased from 27.2% to 50.0%（P trend<0.001）. This trend was also seen in different subgroups stratified by CHA2DS2-VASc score, HAS-BLED score, coronary artery disease type, or management type, and was validated after multivariate adjustment. Persistent atrial fibrillation and history of congestive heart failure, hypertension, diabetes mellitus and stroke/ transient ischemic attack / systemic embolism were the independent predictors of TT/DT use, while ACS, PCI or advanced chronic kidney disease was related with more DAPT prescription. Conclusions There is a shift of antithrombotic regime at discharge for NVAF patients with recent ACS/PCI with reducing DAPT prescription and increasing TT/DT prescription. While the appropriate antithrombotic regimen for NVAF patients with ACS/PCI is still underused in China.